Endoscopic retrograde cholangiopancreatography combined with extracorporeal shock wave lithotripsy for the removal of large gallbladder stones: a pilot study - Liang Zhu; Jinli He; Zhenzhen Yang; Xi Huang; Junbo Hong; Xiaojiang Zhou; Youxiang Chen; Guohua Li (BMC Gastroenterology)
Abstract Background Endoscopic gallbladder-preserving cholecystolithotomy (EGPC) has become an alternative option for treating cholecystolithiasis. However, developing a new method of EGPC in which the gallbladder wall is not damaged remains a challenge. This study introduced a new EGPC method called endoscopic retrograde cholangiopancreatography (ERCP) combined with extracorporeal shock wave lithotripsy (ESWL), which preserves the integrity of the gallbladder wall in the treatment of cholecystolithiasis complicated with choledocholithiasis. Methods In total, six patients (aged 23–72 years, 3 males and 3 females, Han ethnicity) who had large gallbladder stones (diameter ≥ 1 cm) complicated with common bile duct (CBD) stones and who underwent ERCP combined with ESWL at the First Affiliated Hospital of Nanchang University from July 2022 to December 2022 were enrolled. The patients’ clinical characteristics, endoscopic treatment and follow-up data were analyzed. A paired t test was performed to compare the differences in the main serological indicators before and after EGPC. Results Of the six patients, five completed EGPC, and one failed due to intolerable abdominal pain during ESWL and was subsequently transferred to surgery. With respect to post-EGPC adverse events, one patient developed mild post-ERCP pancreatitis, and no other adverse events occurred. Both the technical success rate and clinical success rate of ERCP combined with ESWL were 83.3% and the incidence of adverse events was 16.7%. The six patients were followed up for an average of 24 months, during which only one patient experienced a recurrence of gallbladder stones at the 3-month follow-up, but no gallbladder stones were found at the 6-month follow-up after oral administration of ursodeoxycholic acid. Conclusions ERCP combined with ESWL is a potentially safe and effective treatment for large gallbladder stones. Trial registration This study was registered at the Chinese Clinical Trial Registry site. [Registration number: ChiCTR2200060927 ( http://www.chictr.org.cn/ ); registration date: June 14, 2022].